Comparison of the Visual Outcomes of an Extended Depth-of-Focus Lens and a Trifocal Lens - Moshirfar M (Dove Medical Press, 2021)
Majid Moshirfar,1– 3 James Ellis,4 Daniel Beesley,5 Shannon E McCabe,1,6 Adam Lewis,7 William B West Jnr,4 Yasmyne Ronquillo,1 Phillip Hoopes Snr1 1Hoopes Vision Research Center, Hoopes Vision, Draper, UT, USA; 2John A. Moran Eye Center, Department of Ophthalmology and Visual Sciences, University of Utah, Salt Lake City, UT, USA; 3Utah Lions Eye Bank, Murray, UT, USA; 4University of Utah School of Medicine, Salt Lake City, UT, USA; 5Brigham Young University, Provo, UT, USA; 6Mission Hills Eye Center, Pleasant Hill, CA, USA; 7Kansas City University College of Osteopathic Medicine, Kansas City, MO, USACorrespondence: Majid MoshirfarHoopes Vision Research Center, Hoopes Vision, Draper, UT, USATel +1 801-568-0200Fax +1 801-563-0200Email cornea2020@me.comPurpose: To compare the visual performance of the AcrySof IQ PanOptix trifocal intraocular lens and the TECNIS Symfony extended depth-of-focus lens at near and distance visual ranges.Methods: A total of 146 patients (221 eyes) who underwent phacoemulsification and cataract extraction and received either a PanOptix or Symfony lens from January 2019 to July 2020 were included in the study (83 PanOptix non-toric, 30 PanOptix toric, 70 Symfony non-toric, and 38 Symfony toric). Uncorrected distance (UDVA), uncorrected near (UNVA), and corrected distance (CDVA) visual acuity were assessed at one-day, one-month, and three-months postoperatively. Averages of UDVA, UNVA, and CDVA were taken to evaluate which lens was superior at near and distance visual ranges. Secondary outcome measures including glare, halo, dryness, and problems with night vision were documented at each postoperative visit.Results: At one month postoperatively, the average UNVA was 0.16 ± 0.14 logMAR in the PanOptix group and 0.21 ± 0.14 logMAR in the Symfony group (P=0.007); the average UDVA for the PanOptix group was 0.09 ± 0.13 logMAR compared to the Symfony group at 0.10 ± 0.14 logMAR (P=0.67); and the average CDVA was 0.02 ± 0.05 logMAR in the PanOptix group and 0.00 ± 0.04 logMAR in the Symfony group (P=0.11). At three months postoperatively, there were no statistically significant differences in UNVA, UDVA, or CDVA between the two groups (P=0.18, 0.79, 0.68 respectively). There was no statistically significant difference in secondary outcome measures at one- and three-months (P=0.49, 0.10 respectively).Conclusion: The AcrySof IQ PanOptix trifocal intraocular lens appears to afford better UNVA compared to the TECNIS Symfony extended depth-of-focus intraocular lens at one-month postoperatively, though this difference was not seen at three months postoperatively. There is no statistically significant difference in UDVA and CDVA between the two groups at postoperative day one, one-month, and three-months.Keywords: visual acuity, intraocular lens, trifocal lens, extended depth-of-focus lens